Un análisis de los estudios acerca de las memorias de sostenibilidad en Latinoamérica - Sepúlveda Alzate, Yully Marcela (2018)
The purpose of this document is initially related to the identification of academic publications on sustainability reports, in particular those that link the referents of the Global Reporting Initiative [GRI] and which are intended to study business contexts in Latin America, for later Characterize the publications found. For this purpose, 18 articles published between 2006 and 2016 were collected in the databases of EBSCO, JSTOR and ScienceDirect. The research developed is quantitative and qualitative with a descriptive approach, firstly, quantitative because it makes use of bibliometric techniques that allow to determine where the literature focuses in this field and, qualitatively because it is based on a review of content analysis. The results indicate that most of the studies have focused on evaluating the use of sustainability reports as a management reporting tool, mainly considering the number of indicators, the model chosen or adapted and the periodicity and depth of the information.